Analisis Penggunaan Media Digital Terhadap Tingkat Penjualan Produk Kuliner Kemasan di Kalangan Wirausaha - Uktafiya Nurhayati; Munawaroh Munawaroh (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
This study aims to analyze the influence of digital media on social media in the use of sales levels as an intervening variable. In today's technological era, new business models have emerged as innovations from conventional marketing shifting to modern marketing using digital media. The conventional buying and selling process that requires sellers and buyers to meet face to face can now be mediated by digital media, resulting in new marketing trends. This study uses primary data from distributing questionnaires to entrepreneurs. The sample in this study was 50 respondents with a sampling technique using a purposive sampling approach. There are two variables, namely the Use of Digital Media (X) and Sales Level (Y). The method used in this study is Path Analysis using a data analysis tool, namely SPSS 26. This study aims to determine the influence of the use of digital media on the level of sales of packaged culinary products among entrepreneurs.